Left hemiparesis due to space-occupying lesion in pregnancy - Luminto; Ekarini Aryasatiani; Mahendro Aji Panuntun; Bobby Wirawan Hassan; Tania Sananta; Arya Elbert Neil (Majalah Obstetri dan Ginekologi)
HIGHLIGHTS